KONTRIBUSI KECEPATAN DAN KELINCAHAN TERHADAP KEMAMPUAN DRIBBLING DALAM SEPAKBOLA DI SMA NEGERI 1 BUNUT - Rizki Saufitra; Zainur Zainur; Agus Sulastio (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problem in this study is based on field observations on the football team at SMA Negeri 1 Bunut seen when doing dribbling. This study aims to test whether there is a contribution of speed and agility to dribbling skills in football at SMA Negeri 1 Bunut. The sampling technique was the entire population (total sampling), amounting to 14 people. Based on the results of research conducted from the calculation of the X and Y contribution analysis, it can be concluded that there is a contribution of 11.6% between speed and dribbling ability, 1 person in the very good category is 7.14%, 3 people in the good category are 2.43 %, 6 people in the medium category were 42.86% and 4 people were in the poor category at 28.75%. then there is a contribution of 1.04% between agility to dribbling ability, 12 people in the good category of 85.71%, and 2 people in the moderate category of 14.28%. And there is a contribution of 48.2% between speed and agility to dribbling ability, 14 people with good category at 100%.Key Words: speed, agility, dribbling SMA Negeri 1 Bunut